Evaluation of carbon nanotube x‐ray source array for stationary head computed tomography. Issue 3 (2nd February 2021) - Spronk, Derrek; Luo, Yueting; Inscoe, Christina R.; Lee, Yueh Z.; Lu, Jianping; Zhou, Otto
Abstract : Purpose: Stationary computed tomography (s‐CT) conceptually offers several advantages over existing rotating gantry‐based CT. Over the last 40 yr, s‐CT has been investigated using different technological approaches. We are developing a s‐CT system specifically for head/brain imaging using carbon nanotube (CNT)‐based field emission x‐ray source array technology. The noncircular geometry requires different assessment approaches as compared to circular geometries. The purpose of the present study is to investigate whether the CNT source array meets the requirements for stationary head CT (s‐HCT). Methods: Multiple prototype CNT x‐ray source arrays were manufactured based on the system requirements obtained from simulation. Source characterization was performed using a benchtop setup consisting of an x‐ray source array with 45 distributed focal spots, each operating at 120 kVp, and an electronic control system (ECS) for high speed control of the x‐ray output from individual focal spots. Due to the forward‐angled geometry of the linear anode, the projected focal spot shape is expected to vary at wide angle views. A pinhole method was implemented to determine the effective focal spot size (FSS) in the imaging plane at a range of angular viewpoints with a flat panel detector. The output spectrum and half value layer (HVL) were also evaluated for a range of viewing angles to characterize the beam quality across the fan‐beam. Dosimetry was performed on a simulated scan to evaluate total exposure. Results: The prototype CNT x‐ray source array demonstrated adequate specifications for a s‐HCT imaging machine. The source array was operated at 120 kVp with long‐term stability over a full year of regular laboratory use. Multiple cathode current measurements were used to confirm submicrosecond accuracy with regards to exposure time and subsequently dose control. All 45 focal spots were measured with an average value of 1.26 (±0.04) mm × 1.21 (±0.03) mm (equivalent to IEC 1, 0). The x‐ray spectrum was found to be appropriately filtered based on sources used in existing rotary CT systems. A stable and reliable output of 0.04 mAs per emitter and a resulting dose of 0.015 mGy per projection were observed over several months of rigorous phantom imaging. Dose per projection was regulated by the ECS and measured with ±0.5% tolerance. Conclusions: The CNT x‐ray source array was found to meet the requirements for the proposed stationary head CT scanner, with regard to FSS, beam quality, and dose precision. The remaining challenges are related to the overall system design of a nonrotating CT scanner with distributed sources. The next phase of the project will incorporate multiple CNT source arrays with multirow detectors in a proof‐of‐concept study and analysis of a fully functional s‐HCT system.